Synthesis and Magnetic Properties of [Ni3(BTC)2(H2O)12]n (BTC = 1,3,5-Benzenetricarboxylate) - Bi, Jian-Hong; Li, Meng; Yao, Zi-Lu (Asian Journal of Chemistry, 2011)
A self-assembled coordination polymer with the composition, [Ni3(BTC)2(H2O)12]n (BTC = 1,3,5- benzenetricarboxylate radical) has been synthesized and characterized by IR spectra and elemental analysis. The magnetic properties shows that there are weak antiferromagnetic interactions between the Ni(II) ions of in molecule of the coordination polymer.